Leadership roles of teacher trainees in the Gambia primary school : a case study of two primary schools - Jabbi, Alhagie (2015)
The topic of this Master´s Thesis is the leadership roles of teacher trainees in The Gambia primary: A case study of two primary schools in region two (2). The purpose of this research is to find out whether leadership responsibilities of teacher trainees is developing their education in teaching practice or if it is affecting the quality of teaching and learning in the primary schools. The data of this research were gathered by using semi-structured interviews. The informants are from two primary schools, Farato-Busumbala Lower Basic and Brufut Basic Cycle, The Gambia College and Regional Education Office. From each school five people were interviewed, three teacher trainees, one mentor and one head teacher, two senior education officers from the regional office and two senior lecturers from Gambia College. The interviews were tape recorded and transcribed. I used content analysis to analyze the preliminary findings. Two themes emerged from the findings as leadership roles assigned to teacher trainees which are Classroom Management and Extra Curricular Activities. The research found that teacher trainees are assigned with leadership responsibilities and these roles does not affect their teaching practice instead they develop them to become more effective when they become qualified teachers and assume full teaching responsibilities